6 - Senghor et la pensée de l’universel : l’éclairage leibnizien - Diagne, Ramatoulaye (Africa Development, 2021)
To grasp the depth and originality of Léopold Sédar Senghor’s thought, it is necessary to focus on its sources. Among these sources, Senghor himself often refers to writers such as the Reverend Teilhard de Chardin and Henri Bergson. Senghor, however, never mentioned the German philosopher Gottfried Leibniz. Yet, Leibniz’s conception of universality is very close to Senghor’s, as we will illustrate in this article.